Ecosystem Coupling and Ecosystem Multifunctionality May Evaluate the Plant Succession Induced by Grazing in Alpine Meadow - Wang, Yingxin; Wu, Zhe; Wang, Zhaofeng; Chang, Shenghua; Qian, Yongqiang; Chu, Jianmin; Jia, Zhiqing; Zhou, Qingping; Hou, Fujiang (Frontiers in Plant Science, 2022)
Most alpine meadow on the Tibetan Plateau are at different stages of community succession induced by grazing practices. Quantifying the succession sequence and assessing the dynamics of plant composition, ecosystem coupling, and multifunctionality across successional stages are essential for reasonable restoration of degraded alpine meadow. Here, we selected areas with different grazing disturbance histories and used them as a space series (i.e., space-for-time substitution) to study the community succession. Our work quantified the plant succession sequence of alpine meadow induced by grazing with plant functional group approach. The plant succession sequence is from the tall sedge community with erect growth to the short undesirable toxic forbs community with prostrate growth. Ecosystem coupling, ecosystem multifunctionality and their relationships were all the lowest in Stage 4. Compared to Stage 4, the ecosystem multifunctionality index increased in Stages 1, 2, and 3 by 102.6, 89.8, and 207.6%, respectively; the extent of ecosystem coupling increased by 20.0, 16.8, and 21.2%, respectively. Our results indicated that the driving factors of ecosystem coupling and ecosystem multifunctionality were soil factor individual in early successional stage to plant-soil simultaneously in late successional stage. Our results also highlighted the importance of toxic weeds during the late stage of degraded succession and suggest that the expansion of toxic plants is a consequence of their greater suitability from a successional perspective. The findings of this study would provide valuable guidance for optimizing the management and restoration practice of alpine meadow.